Pengaruh Kualitas Produk dan Brand Image Sepeda Motor Yamaha NMAX Terhadap Keputusan Pembelian di JG Motor Asia Afrika Bandung - Desfitriady, Desfitriady; Novita, Nova (Jurnal Etnik: Ekonomi-Teknik, 2023)
This research was conducted on customers of JG Motor Asia Africa Bandung workshops. The purpose of this research is to find out how much influence the influence of product quality and brand image has on purchasing decisions both partially and simultaneously through Instagram social media. The research method that will be used in this research is descriptive method and associative method. In this study, the unit of analysis is the individual, namely the Customers of JG Motor Workshop Asia Africa Bandung who buy Yamaha NMAX motorcycle products. The sample in this study were 67 respondents. Sampling accidental sampling is the sampling technique used in this study. The analytical method uses multiple linear regression analysis, in addition to testing the validity and reliability of the research instrument. Based on the results of the study, it shows that there is a partial or simultaneous effect on the Product Quality variable with a contribution value of 40.3% on purchasing decisions and 47% contributing to the influence of Brand Image on purchasing decisions. And the effect of Product Quality and Brand Image partially or simultaneously contributes to purchasing decisions of 87.3% while the remaining 12.7% is the influence of other variables not examined.